Synthesis of Light-Emitting Conjugated Polymers for Applications in Electroluminescent Devices - Grimsdale, Andrew C; Leok Chan, Khai; Martin, Rainer E; Jokisz, Pawel G; Holmes, Andrew B (Chemical reviews, 2009)
A discussion of electroluminescent polymers and their application in electrical devices is presented. The structure of these materials and how their properties can be controlled are explored.